Impact of cadmium salt concentration on cds nanoparticles synthesized by chemical precipitation method - Najm A.S.; Chowdhury M.S.; Munna F.T.; Chelvanathan P.; Selvanathan V.; Aminuzzaman M.; Techato K.; Amin N.; Akhtaruzzaman M. (S.C. Virtual Company of Phisics S.R.L, 2023)
In this study, cadmium sulfide (CdS) nanoparticles (NPs) were synthesized via chemical precipitation, a facile and cost effective method. The effects of various cadmium salt concentration on the characteristics of CdS NPs has been analyzed to understand the structure properties relationship for optoelectronics applications. XRD, FESEM, Raman Spectra, and UVVis has been used to characterize the prepared samples. The optical measurement indicates that there is a direct transition in accordance to energy band gap among 2.36 as well as 2.4 eV. The XRD diffract grams verify that all the films deposited have been polycrystalline of cubic as well as hexagonal structure with superior orientation (111). Analysis of EDX displayed that certain films have been stoichiometric with a small deficiency in sulphur. By optimizing the molar concentration of cadmium ions, the optoelectronic properties of the CdS NPs can be tuned accordingly. 2020, S.C. Virtual Company of Phisics S.R.L. All rights reserved.